Remote Continuous Microinjury-Triggered Cytokines Facilitate Severe Diabetic Foot Ulcer Healing via the Ras/Raf/MEK/ERK Pathway - Huang X; Liu J; Wu X; Mo Y; Luo X; Yang Y; Yang C; Liang X; Liang R; Chen Y; Fan Z; Lu W; et al. (Journal of Inflammation Research)
Xiajie Huang,1,2,* Jie Liu,1,* Xiaomei Wu,1 Yangzhou Mo,1 Xiping Luo,1 Yongge Yang,1 Chaoquan Yang,1 Xinyun Liang,1 Rongyuan Liang,1 Yeping Chen,1 Zezhen Fan,1 William Lu,3 Yan Chen,1 Qikai Hua1 1Department of Bone and Joint Surgery, The First Affiliated Hospital of Guangxi Medical University, Nanning, People’s Republic of China; 2Collaborative Innovation Centre of Regenerative Medicine and Medical BioResource Development and Application Co-Constructed by the Province and Ministry, Guangxi Medical University, Nanning, People’s Republic of China; 3Department of Orthopaedics and Traumatology, The University of Hong Kong, Hong Kong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan Chen; Qikai Hua, Department of Bone and Joint Surgery, The First Affiliated Hospital of Guangxi Medical University, Nanning, People’s Republic of China, Email cy003@connect.hku.hk; hqk100@yeah.netPurpose: Microinjury can trigger in situ tissue repair. Bone transport consists of continuous microinjuries/microfracture and induces bone formation and angiogenesis. Tibial cortex transverse transport (TTT) was found to promote angiogenesis at the foot and the healing of diabetic foot ulcers (DFUs). However, the underlying mechanism remains largely unknown.Methods: We divided 72 Sprague-Dawley rats with DFUs into the control, sham, and TTT groups. Wound measurement and histology were performed to evaluate the wound healing processes. Enzyme-linked immunosorbent assay, flow cytometry, immunohistochemistry, and Western Blot were used to assess angiogenesis and the activity of endothelial progenitor cells (EPCs) and the Ras/Raf/MEK/ERK signaling pathway.Results: We found accelerated wound healing, improved epidermal continuity, and increased dermal thickness in the TTT group than the control and the sham groups. Higher levels of serum TGF-β 1, PDGF-BB, and VEGF were detected in the TTT group. These changes were in parallel with the expression of TGF-β 1, PDGF-BB, and VEGF in the foot wounds and the frequency of EPCs in both bone marrow and peripheral circulation, which implied that the secreted TGF-β 1, PDGF-BB, and VEGF promote proliferation and migration of EPCs to the foot wounds. The expression of CD31+ cells, SMA-α+ cells, and the Ras/Raf/MEK/ERK pathway was higher in the TTT group than in the control and sham groups.Conclusion: The findings showed that TTT enhanced the production of growth factors that in turn activated EPC proliferation and migration through the Ras/Raf/MEK/ERK pathway, ultimately contributing to angiogenesis and DFU healing. Based on these findings, we proposed a theory that remote continuous microinjuries can trigger the repair of target tissues (ie, microinjury-induced remote repair, MIRR). Future studies are needed to validate this theory.Keywords: microinjury, bone transport, tibial cortex transverse transport, diabetic foot ulcer, endothelial progenitor cells, Ras/Raf/MEK/ERK signaling pathway